Is potassium thiosulfate a poison? Is it safe? A case series - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2017)
Potassium Thiosulfate is a liquid substance used for producing fertilizers. In this case series, we present five patients who have been exposed to potassium thiosulfate inhalation. Three of them were intubated in the scene by paramedics because of confusion and respiratory depression. They had refractory status epilepticus. The other two were exposed during trying to help the others for getting out, they presented to ED with nausea, vomiting and headache. One of the intubated patients died on the 4th day of his follow-up at ICU. Others were sent home after few days with no complication. Potassium thiosulfate is not a substance documented for poisoning and it is assumed to be a safe and stable solution. Although, it was assumed to be a safe substance there are risks of metabolic acidosis, resistant generalized seizures, and death due to disturbance of oxidative reactions with potassium thiosulfate.
Keywords: Potassium thiosulfate; Poisoning; Metabolic acidosis; H2S; Case series; HYDROGEN-SULFIDE; MITOCHONDRIA